Excitations of the 4F and 5F States of Atomic Hydrogen by Positron Impact (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2024)
The excitation cross sections of the 4F and 5F states of atomic hydrogen by positron impact have been calculated at low incident energies (from 1.00 to 4.41 Ry), using the variational polarized method, also called the hybrid theory. Partial waves ranged from \(L=3\) to 20 to obtain converged cross sections. The importance of the long-range interaction in the threshold region is discussed. A comparison of \(S\), \(P\), \(D\), and \(F\) cross sections is given. These cross sections are needed because of cascades from higher states to the \(S\) state when the cross sections of the \(S\) state in hydrogen are measured or in diagnostics of solar and astrophysical observations. The phase shifts at low energies are also given.
Keywords: Hybrid theory; Excitation cross sections; Phase shifts